Penerapan Aplikasi Warung Media Berbasis Android Guna Meningkatkan Promosi dan Penjualan - Sudianto, Aris; Wijaya, Lalu Kerta; Jumawal, Jumawal; Mahpuz, Mahpuz (Infotek: Jurnal Informatika dan Teknologi, 2024)
Warung Media is a start-up that provides various media needs such as laptop repair services, graphic design, videography, and all media needs that can be requested by yourself. Media stalls take advantage of technological developments to market their services online, namely through social media and offline. The design of this media shop application is a step to increase sales and promotion of service products offered by the media shop so that it can provide more benefits for the media shop itself. The purpose of building this system is so that customers can order products online and as a promotional media as well as more value from media stalls. In addition, with this application, users can easily see the products offered by media stalls. This system is designed using the java programming language and using the android studio application. The results of this study are the media shop application which is used as a means of sales promotion that can be accessed anywhere and anytime, the service ordering process can be done directly without having to come to the place, and can facilitate the process of buying services transactions, so as to increase sales of services from media stalls